Design Challenges for High-Speed Digital Links for Automotive Applications - Hernandez-Bonilla, Jose Enrique; Klein, Christian; Alavi, Golzar; El Ouardi, Abdessamad; Reuschel, Torsten; Schuster, Christian (IEEE electromagnetic compatibility magazine, 2024)
This paper outlines the state of the art and future directions for high-speed links in modern automotive applications. The technological constraints of signal integrity (SI) are discussed in the context of challenges of the mechanical and atmospheric environment. The requirements are illustrated by example of automotive Ethernet and its use to establish communication between electronic control units (ECUs). The overview covers design elements and parts inside the ECU enclosure as well as the link segment in between control units. Moreover, the compound system is subject to operational testing and verification of compliance with applicable standards.